2011
DOI: 10.1124/jpet.111.182055
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vimentin in the Inhibitory Effects of Low-Molecular-Weight Heparin on PC-3M Cell Adhesion to, and Migration through, Endothelium

Abstract: Low-molecular-weight heparin (LMWH) has been used in cancer patients with venous thromboembolic complications, resulting in a higher survival rate and an inhibitory action on experimental metastasis. In the present study, human umbilical vein endothelial cells (HUVECs) were treated with LMWH for 24 h. We found that the resulting HUVECs could significantly inhibit the highly metastatic human prostate cancer cell line (PC-3M) in terms of its adhesion to the endothelium and migration across the endothelium, accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…found that vimentin could be regulated by LMWH and played a critical role in the antiangiogenesis and antimetastasis effects of LMWH (Pan et al, 2011). In the present study, we found that vimentin activity was influenced in the group administered enoxaparin with gefitinib in A549 cells (Fig.…”
Section: Sensitization Of Lung Cancer Cells By Enoxaparin To Gefitinibsupporting
confidence: 63%
See 3 more Smart Citations
“…found that vimentin could be regulated by LMWH and played a critical role in the antiangiogenesis and antimetastasis effects of LMWH (Pan et al, 2011). In the present study, we found that vimentin activity was influenced in the group administered enoxaparin with gefitinib in A549 cells (Fig.…”
Section: Sensitization Of Lung Cancer Cells By Enoxaparin To Gefitinibsupporting
confidence: 63%
“…Our previous study showed that unfractionated heparin does not easily cross the cell membrane (Pan et al, 2011). Therefore, it is possible for enoxaparin to exert its function through interaction with proteins present on the cell surface, including DOCK1, which could be translocated across the plasma membrane (Kobayashi et al, 2001).…”
Section: Sensitization Of Lung Cancer Cells By Enoxaparin To Gefitinibmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, based on the hypothesis that heparin regulates vimentin in the tumor-endothelium interaction and the finding of endothelial 2-DE experiment that vimentin expression altered greatly by low molecular weight heparin, we demonstrated that vimentin partly plays a role in the anti-metastatic effects of low molecular weight heparin [16] . In the present study, we further analyzed and confirmed the down-regulated expression of vimentin, which was also one of the proteins influenced by heparin and identified in both the PC-3M cells and lungs of mice burdened with B16-F10-luc-G5 cells, along with 14-3-3 zeta/delta.…”
Section: Effect Of Heparin On Brdu Incorporation and Ki67 Expression mentioning
confidence: 99%